The Effect of The Use of Dragon Fruit Powder Fermented By Yeast Saccharomyces cerevisiae in The Rations Toward Broiler Carcass Production - I K. S. A., Putra; Dewi, G. A. M. K.; Utami, I. A. P. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This study aimed to determine the effect of the use of fermented dragon fruit powder by using yeast Saccharomyces cerevisiae toward the production of carcass broiler. The research was conducted at Research Station of Faculty of Animal Husbandry Udayana University, Jimbaran, Badung, Bali, for 5 weeks. This research used broilers type MB 202taken from PT Japfa Comfeed Indonesia Tbk which were 1 week old as many as 90 with a homogeneous weight. The design used was Completely Randomized Design (CRD) with 3 treatments and 6 replications, in which each replication consisted of 5 broiler aged 1 week. The treatments tried in this study were RKBN0: the ration was without dragon fruit skin, RKBN1: the ration had 5% fermented dragon fruit skin, RKBN2: the ration had 7% fermented dragon fruit skin. The variables observed were the weight of carcass, percentage of carcass, chest weight, thigh weight, wing weight and weight of back. The results showed that the chest weight with treatment of RKBN1 and RKBN2 had significant effect (P<0.05) compared to RKBN0 treatment while the weight of carcass, percentage of carcass, thigh weight, wing weight and weight of back had no significant effect (P>0,05) compared to RKBN0 treatment. Based on the results of the study it can be concluded that the administration of 5% and 7% dragon fruit skin flour fermented by Saccharomyces cerevisiae has an effect on chest weight and does not affect the production of carcass and other carcass parts.   Keywords: rations, dragon fruit, fermentation, carcass production, broiler